The use of bioelectrical impedance analysis to estimate total body water in young children with cerebral palsy - Bell, K.; Boyd, Roslyn; Walker, J.; Stevenson, R.; Davies, P. (2013)
Background & aims: Body composition assessment is an essential component of nutritional evaluation in children with cerebral palsy. This study aimed to validate bioelectrical impedance to estimate total body water in young children with cerebral palsy and determine best electrode placement in unilateral impairment. Methods: 55 young children with cerebral palsy across all functional ability levels were included. Height/length was measured or estimated from knee height. Total body water was estimated using a Bodystat 1500MDD and three equations, and measured using the gold standard, deuterium dilution technique. Comparisons were made using Bland Altman analysis. Results: For children with bilateral impairment, the Fjeld equation estimated total body water with the least bias (limits of agreement): 0.0L (-1.4L to 1.5L); the Pencharz equation produced the greatest: 2.7L (0.6L-4.8L). For children with unilateral impairment, differences between measured and estimated total body water were lowest on the unimpaired side using the Fjeld equation 0.1L (-1.5L to 1.6L)) and greatest for the Pencharz equation. Conclusions: The ability of bioelectrical impedance to estimate total body water depends on the equation chosen. The Fjeld equation was the most accurate for the group, however, individual results varied by up to 18%. A population specific equation was developed and may enhance the accuracy of estimates. Australian New Zealand Clinical Trials Registry (ANZCTR) number: ACTRN12611000616976. © 2012 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism.